2000
DOI: 10.1111/j.1475-2743.2000.tb00196.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of municipal compost on temperature, water, nutrient status and the yield of maize in a temperate soil

Abstract: Abstract. Composted domestic waste was applied either as a mulch or was incorporated into the topsoil. Mulching reduced the seasonal midday soil temperature ranges from between 14 °C and 27.5 °C to between 14 °C and 26 °C, averaging a 0.6 °C fall. However, at sub‐optimal temperatures for maize production under the temperate conditions of South East England, the difference may be critical. Compost mulch also improved soil‐water conservation in an average year, but not in a very dry year. Compost application in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Bationo et al (1993) had earlier reported similar significant millet yield responses in the second year of crop residue application. The probable explanation of the residual effect of mulching to the following year could be the enhanced supply of nutrients and water through nutrient recycling, wind-blown dust trapping, and reduced evaporation (Movahedi Naeni and Cook 2000;Ram et al 2003;Schlecht et al 2006). This residual effect may also explain the significant interaction between mulch and year on yields (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Bationo et al (1993) had earlier reported similar significant millet yield responses in the second year of crop residue application. The probable explanation of the residual effect of mulching to the following year could be the enhanced supply of nutrients and water through nutrient recycling, wind-blown dust trapping, and reduced evaporation (Movahedi Naeni and Cook 2000;Ram et al 2003;Schlecht et al 2006). This residual effect may also explain the significant interaction between mulch and year on yields (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that manure is rich in readily available C, N and other macro-and micro-nutrients that microorganisms require for their growth and activities (Feikea et al, 2009;Gupta et al, 1992), there are also various effects of manure that microbes can profit from. For instance, manure application can maintain soil moisture and ease rapid changes in soil temperature (Naeini and Cook, 2000), which helps to provide a stable environment for soil microbes to growth.…”
Section: Overall Response Of Soil Microbial Biomass To Manure Applicamentioning
confidence: 99%
“…Incorporating organic matter [10][11][12], nutrients and electrolytes into the soil [13]; reducing the need for fertilizers [14], pesticides and peat use [15], activating a wide ranges of natural disease suppressiveness mechanisms against plants pathogens and bio stimulation able to improve the overall plant status [16]; improving soil structure, density and porosity [17][18][19][20][21][22][23][24][25], which increase water retention capacity and reduce erosion and nutrient leaching [20,26]; and enhancing carbon storage capacity in the soil, thus, reducing global warming [24,27,28].…”
Section: Introductionmentioning
confidence: 99%